Hydraulics - Simon, Andrew L. (Prenctice Hall, 1997)
Encompassing basic fluid mechanics and the properties of liquids through to coastal and machinery hydraulic applications, this textbook covers a very wide field of study. The authors assume that students will be using commercially available software.